P126 Tolerability, efficacy and adherence: what do lupus patients think about treatment?. (23rd March 2020) - Navarro, Elvira Chocano; Robinson, George; Gutierrez, Lucia Martin; McDonnell, Thomas; Waddington, Kirsty; Jury, Elizabeth; Ciurtin, Coziana; Wincup, Chris
Abstract : Background: The treatment of systemic lupus erythematosus (SLE) can be challenging due to the complex nature of symptoms, yet despite recent advances in treatment, patients' opinion and medication beliefs are poorly understood. Furthermore, patient understanding of treatment plays a major role in medication adherence. In this study we aimed to understand patient experiences relating to treatment. Methods: Thirteen patients attended a patient engagement event. They were asked to answer 12 structured treatment-based questions designed to assess medication beliefs. Round table discussions were held where patients shared their experiences to allow for both qualitative and quantitative data collection. Results: The majority of patients (74.5%) believed that they had a good understanding of their current treatment with many accessing medication-related information though consultation with their rheumatologist or specialist nurse (93.3%), via patient information sheets (33%) and by using online resources (46.6%). Many patients (76.9%) reported that they had concerns before starting a new treatment, in particular in relation to potential side effects and ultimate treatment duration. A substantial number (75%) of patients reported a previous adverse reaction or side effect to treatment. Just over half of participants (54.6%) were previously advised by their doctor to stop taking a medication because it was not effective. Interestingly, 40% said they had stopped taking their medication on their own accord, usually due to side effects, with 54.5% reported stopping treatment due to feeling it to be ineffective. Figure 1 shows 'World Cloud' qualitative analysis of patient responses regarding concerns prior to starting treatment. Figure 2 shows perceived side effects reported by participants. Over 90% of respondents thought more research should be performed in investigating potential side effects and to identify those who will respond well prior to starting a treatment. Conclusions: In summary this work shows that patients are concerned about adverse events associated with treatment and supports new research to identify ways to mitigate those effects.